‘How were the traces of their edifices erased?’ Archaeological / ethno-historical survey of Jerba, Tunisia - Holod, Renata (Khalili Research Centre Seminars, 2017)
Keywords: Archéologie -- Djerba

Guarding a Well-Ordered Space on a Mediterranean Island - Holod, Renata; Kahlaoui, Tarek (The Archaeology of Medieval Islamic Frontiers, 2019)
For Ifriqiya, the Maghrib, and the eastern coast of al-Andalus, a ribāṭ can be defined as a coastal point of defense meant to host ghazīs, warriors for the faith or volunteers on the basis of religious commitment. From the eighth century onward, ribāṭs stretched along the seashore of Islamic Maghrib from Tripoli (Ṭarāblus) up to the east coast of al-Andalus. These were typically connected to another urban structure with an immediately supporting rural environment, or they could be isolated structures supplied from the sea. In one sense, they functioned in much the same way as stations along the ‘Abbasid-Byzantine land
Keywords: Archéologie -- Djerba; Hâra, mosquée al- (Sedouikech, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba)

Towns and ports - Fentress, Elizabeth (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie -- Djerba

Water supply in the Roman period: aqueducts and cisterns - Wilson, Andrew (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

Islamic Pottery from Jerba (7th-10th century): Aspects of Continuity? - Cirelli, Enrico; Holod, Renata (La céramique maghrébine du haut Moyen Âge (VIII-X siècle): état des recherches, problemes et perspectives, 2011)
Keywords: Antiquité; Archéologie -- Djerba

Recherches sur le mausolée hellénistique d’Hinshīr Būrgū - Ferchiou, Naïdé (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

The forts - Fentress, Elizabeth (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

Les sources - Drine, Ali (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie -- Djerba

La ceramica tra l’età punica e la tarda antichità. Le anfore - Fontana, Sergio (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

The punic and libyan cemeteries - Ben Tahar, Sami (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

An island through time: Jerba studies - Fentress, Elizabeth; Drine, Ali; Holod, Renata; Aït Kaci, Ahmed (Journal of Roman Archeology. Supplements, 2009)
Keywords: Archéologie -- Djerba; Monuments -- Djerba; Sidi Garus, mosquée (Haddada, Djerba); Sidi Jmur, mosquée (El Groo, Djerba)

The excavations at Meninx-Tala - Aït Kaci, Ahmed (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie -- Djerba

The sacred landscape - Aït Kaci, Ahmed (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie -- Djerba

The rural landscape and economy - Fentress, Elizabeth; Fontana, Sergio (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

La ceramica a Jerba tra l’Età Punica e la Tarda Antichità - Capelli, C.; Ben Tahar, Sami; Fontana, Sergio (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

The towns and ports - Fentress, Elizabeth; Drine, Ali; Morton, Thomas; Ghalia, T. (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba